2018
DOI: 10.3758/s13428-018-1134-4
|View full text |Cite
|
Sign up to set email alerts
|

The human task-evoked pupillary response function is linear: Implications for baseline response scaling in pupillometry

Abstract: The human task-evoked pupillary response provides a sensitive physiological index of the intensity and online resource demands of numerous cognitive processes (e.g., memory retrieval, problem solving, or target detection). Cognitive pupillometry is a wellestablished technique that relies upon precise measurement of these subtle response functions. Baseline variability of pupil diameter is a complex artifact that typically necessitates mathematical correction. A methodological paradox within pupillometry is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 52 publications
(70 reference statements)
3
82
0
Order By: Relevance
“…Reilly, personal communication, July 1, 2019), we confirmed that this Reilly et al, (2019) obtained their luminance values by using the subject view. Therefore, it would be good practice to be very explicit about how luminance values are obtained for anyone doing pupillometry researchsomething we will do in future publications.…”
Section: Methodological Implicationssupporting
confidence: 80%
“…Reilly, personal communication, July 1, 2019), we confirmed that this Reilly et al, (2019) obtained their luminance values by using the subject view. Therefore, it would be good practice to be very explicit about how luminance values are obtained for anyone doing pupillometry researchsomething we will do in future publications.…”
Section: Methodological Implicationssupporting
confidence: 80%
“…Although studies in cognitive pupillometry traditionally focus on the change in pupil size relative to baseline (the task-evoked pupillary response; see Reilly et al, 2018), several studies have focused on the BPD itself. Unlike the task-evoked pupillary response that is measured during or after an experimental trial, the BPD is a measure taken prior to an experimental trial.…”
Section: Introductionmentioning
confidence: 99%
“…Next, a five-point moving average was used to smooth the data. The smoothed data was then normalized with subtractive baselining (Reilly, Kelly, Kim, Jett, & Zuckerman, 2019) . The baseline for each trial was the median value of the 500 ms immediately preceding the beginning of the stimulus.…”
Section: Methodsmentioning
confidence: 99%